Tingkat Adaptif Tata Kelola Pemerintahan Indonesia Dalam Menghadapi Perubahan Iklim - Abdi, Azizah Putri; Rasdiana, Rasdiana; Radhinal , Yan; Hadid, Adina Khusnudzan; Halim, Muhammad Adhim (JURNAL RUANG / ISSN : 2085-6962, 2025)
Indonesia is a country that is vulnerable to natural disasters such as climate change, where climate change is a complex and unpredictable issue and has a major impact on community welfare and political stability, requiring a strong and adaptive governance system that can be used as a solution in facing the challenges of rapid global change. Therefore, this study aims to determine the adaptive level of Indonesian governance in dealing with climate change. The data used in this study uses secondary data sourced from research studies and research theories. The analysis technique used in this study is the systematic literature review method. The results of this study indicate that Indonesian government governance is characterized by flexibility because it has advantages in community empowerment and involvement as well as knowledge and decision-making but lacks coordination between actors and leadership capacity.